2019
DOI: 10.3758/s13415-019-00720-4
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of well-being: A systematic review of the human neuroimaging and neuropsychological literature

Abstract: What it means to be well and to achieve well-being is fundamental to the human condition. Scholars of many disciplines have attempted to define well-being and to investigate the behavioral and neural correlates of well-being. Despite many decades of inquiry into well-being, much remains unknown. The study of well-being has evolved over time, shifting in focus and methodology. Many recent investigations into well-being have taken a neuroscientific approach to try to bolster understanding of this complex constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 70 publications
0
46
1
Order By: Relevance
“…The GENIAL model of wellbeing ( Genomics - Environment - vagus Nerve - social Interaction - Allostatic regulation – Longevity) , proposes that vagal function may underpin pathways to health, wellbeing and longevity ( Kemp et al, 2017 ). There is now substantial evidence that each of the core domains of wellbeing has been shown to both affect and be affected by vagal function ( Kringelbach and Berridge, 2010 ; King, 2019 ; Fisher et al, 2020 ). In a recent review on wellbeing and the neurological disorders ( Fisher et al, 2020 ), we proposed several core domains of wellbeing, comprising the individual (including a balanced mind and a healthy body), community (social connection), the natural environment (connection with nature), the role of behaviour change and socio-structural factors, which are summarised below.…”
Section: Introductionmentioning
confidence: 99%
“…The GENIAL model of wellbeing ( Genomics - Environment - vagus Nerve - social Interaction - Allostatic regulation – Longevity) , proposes that vagal function may underpin pathways to health, wellbeing and longevity ( Kemp et al, 2017 ). There is now substantial evidence that each of the core domains of wellbeing has been shown to both affect and be affected by vagal function ( Kringelbach and Berridge, 2010 ; King, 2019 ; Fisher et al, 2020 ). In a recent review on wellbeing and the neurological disorders ( Fisher et al, 2020 ), we proposed several core domains of wellbeing, comprising the individual (including a balanced mind and a healthy body), community (social connection), the natural environment (connection with nature), the role of behaviour change and socio-structural factors, which are summarised below.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that default mode network (DMN) comprises regions such as precuneus, temporoparietal junction (Raichle et al, 2001) and angular gyrus (Igelstrom & Graziano, 2017). Also, covered regions were reported in previous studies that they have significant associations (see review (King, 2019)). Channel coordinates were obtained by using a navigation system on a subject’s head.…”
Section: Methodsmentioning
confidence: 90%
“…Understanding well-being level of individuals is a challenging problem due to being dependent to self-reporting which is a subjective criteria (Diener, 1984). To objectively assess well-being, several neuroimaging studies have been performed to understand the neural correlates of well-being and it was reported that anterior cingulate cortex (ACC), orbitofrontal cortex (OFC), posterior cingulate cortex (PCC), superior temporal gyrus (STG) and thalamus was strongly associated to well-being and these regions are sub-components of default mode network (DMN) (see review (King, 2019)). This finding makes resting state functional connectivity (rsFC) based studies using fMRI (Kong, Liu, et al, 2015; Kong, Wang, et al, 2015; Kong, Wang, et al, 2016; Kong, Xue, et al, 2016; Luo et al, 2014; Luo et al, 2016; Luo et al, 2017; W. Sato et al, 2019) and fNIRS (F. Goldbeck et al, 2018) important to understand the underlying neural mechanisms of well-being.…”
Section: Introductionmentioning
confidence: 99%
“…, 2017 ; Shi et al. , 2018 ; King, 2019 ). In line with the exiting findings, our mediation models revealed that through TSC, the IFG within the ECN could positively affect EWB and negatively predict negative affect in the pandemic, while the precuneus within the DMN could negatively affect EWB and the MFG positively predict negative affect in the pandemic.…”
Section: Discussionmentioning
confidence: 99%